5. Combating Cyber Racism: Analisis Komparatif terhadap Implementasi Protokol Tambahan Council of Europe Convention on Cybercrime tentang Cyber Racism (CETS 189) di Amerika Serikat dan Australia Tahun 2012-2016 - Riani Charlina; Tri Cahya Utama; Nadia Farabi (Journal of International Relations Diponegoro, 2017)
In this globalization era, technological advances undeniably encouraged the developmentof the scope of crime along with the development of science. The phenomenon of crimecommitted in cyberspace, known as cybercrime, is one of the most dangerous crimes thatare currently faced by most people in the world. One of those crimes is racism incyberspace or what so-called cyber racism. The United States and Australia are the twolargest countries out of the Council of Europe member countries which committed toovercome cyber racism by ratifying the Council of Europe Convention on Cybercrime andadditional protocol concerning cyber racism (CETS 189). Nonetheless, there are somedifferences in the implementation of this convention between the United States andAustralia in overcoming cyber racism. This study aims to determine factor that influencesthe differences in the implementation of CETS 189 in the United States and Australia.Using culturalist approach as an analytical lens, this study argues that national law is thecause of the differences in the implementation of CETS 189 in the United States andAustralia. It is affected by cultural factor in which the United States has liberal perceptionregarding freedom of speech, while Australia tends to provide some limits on freedom ofspeech.